Correlation of PET/CT Maximal Standardized Uptake Values with Clinicopathologic Parameters of Aggressive Non-Hodgkin’s Lymphoma - Li Y; Wu D; Tian M (Cancer Management and Research)
Yingci Li,1 Dongbo Wu,2 Mohan Tian1 1Department of PET/CT-MR Center, Harbin Medical University Cancer Hospital, Harbin, Heilongjiang, 150081, People’s Republic of China; 2Department of Radiology, Harbin Medical University Cancer Hospital, Harbin, Heilongjiang, 150081, People’s Republic of ChinaCorrespondence: Mohan Tian, Department of PET/CT-MR Center, Harbin Medical University Cancer Hospital, No. 150, Haping Road, Nangang District, Harbin City, Heilongjiang, 150081, People’s Republic of China, Email mohantianthm@21cn.comObjective: To investigate the correlation between the maximum standardized uptake value (SUVmax) of positron emission tomography (PET)/computed tomography (CT) scanning imaging with the clinicopathologic parameters of aggressive non-Hodgkin’s lymphoma (NHL) and its diagnostic value.Methods: A total of 128 patients with NHL were retrospectively selected. PET/CT examination was performed to calculate SUVmax, and clinicopathological data were collected. Pearson correlation test was used to analyze the correlation between them, and the relevant indicators were detected according to the pathological results. ROC curve was used to analyze the diagnostic value.Results: The level of PET/CT SUVmax was positively correlated with the levels of β 2-microglobulin (β 2-MG), lactate dehydrogenase (LDH), Ki-67, tumor size and bone marrow infiltration (P< 0.05). The PET/CT SUVmax and serum β 2-MG, LDH and Ki-67 levels in the aggressive group were significantly higher than those in the indolent group (P< 0.05). The AUC of the combined detection of PET/CT SUVmax, β 2-MG, LDH and Ki-67 in the diagnosis of aggressive NHL was 0.920, and the combined detection had a high diagnostic value.Conclusion: PET/CT SUVmax was correlated with a variety of clinicopathological parameters. Combined detection of PET/CT SUVmax has high diagnostic value in aggressive NHL.Keywords: PET/CT maximum standardized uptake values, β 2-MG, LDH, Ki-67, aggressive non-Hodgkin’s lymphoma